2004
DOI: 10.1140/epjc/s2004-01870-9
|View full text |Cite
|
Sign up to set email alerts
|

Bose-Einstein correlations for Lévy stable source distributions

Abstract: The peak of the two-particle Bose-Einstein correlation functions has a very interesting structure. It is often believed to have a multivariate Gaussian form. We show here that for the class of stable distributions, characterized by the index of stability 0 < α ≤ 2, the peak has a stretched exponential shape. The Gaussian form corresponds then to the special case of α = 2. We give examples for the Bose-Einstein correlation functions for univariate as well as multivariate stable distributions, and check the mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
131
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 45 publications
1
131
0
2
Order By: Relevance
“…(1.1), ρ 2 is a function of the two fourmomenta. However, BEC are large only when p 1 ≈ p 2 , and it has been found that the correlation function can be adequately parametrized as a function of the four-momentum difference Q, 24) which has the clear advantage of reducing ρ from a six-dimensional function to a one-dimensional one. Hence, two-particle BEC are investigated here using the function…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1.1), ρ 2 is a function of the two fourmomenta. However, BEC are large only when p 1 ≈ p 2 , and it has been found that the correlation function can be adequately parametrized as a function of the four-momentum difference Q, 24) which has the clear advantage of reducing ρ from a six-dimensional function to a one-dimensional one. Hence, two-particle BEC are investigated here using the function…”
Section: Analysis Methodsmentioning
confidence: 99%
“…There have been many discussions (see e.g. [24]) on alternatives to the Gaussian parametrization. However, many of these require model assumptions.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…In previous years, Gaussian-type sources were usually utilized to describe the correlation functions, but the latest results from the PHENIX experiment showed that we can and have to go beyond the Gaussian approximation [6,7]. In an expanding medium, on the basis of the generalized central limit theorem and the anomalous diffusion we can expect the appearance of Lévy-type sources [8,9]. The symmetric Lévy distribution is the generalization of the Gaussian distribution and it is defined by the following expression:…”
Section: Introductionmentioning
confidence: 99%
“…In case of α < 2 the Lévy distribution exhibits a power-law behavior. Neglecting the final-state interactions and assuming that the source is a spherically symmetric three-dimensional Lévy distribution, furthermore using the framework of the core-halo model, the two-particle correlation function takes the following simple form (Q is a one-dimensional relative momentum variable, see details in [9] and in Section 2):…”
Section: Introductionmentioning
confidence: 99%
“…One of the best tools to gain information about the particle-emitting source is the measurement of Bose-Einstein or HBT correlations of identical bosons. In our latest measurements, we utilize Lévy-type sources [4,5] to describe the measured correlation functions. In case of a second order QCD phase-transition, one of the source parameters, the index of stability α is related to one of the critical exponents (the so-called correlation exponent η).…”
Section: Introductionmentioning
confidence: 99%